Continuity under Change in Dayak Societies - Arenz, Cathrin; Haug, Michaela; Seitz, Stefan; Venz, Oliver (Edition Centaurus - Sozioökonomische Prozesse in Asien, Afrika und Lateinamerika,, 2017)
This volume provides a balanced picture of change and continuity within Dayak societies from an anthropological perspective by exploring diverse ways in which certain kinds of knowledge, performances and practices continue within the context of rapid and profound change. The contributions cover a broad variety of topics including political reform, decentralisation, environmental change and related changes in natural resource management, religion and ritual practice, the (re-)formation of ethnic identities as well as conflict transformation in Indonesian Borneo. Contents Human-Environmental Relations Ethnicity, Identity and Conflict Dayak Religion and Animism Target Groups Ethnologists, geographers, historians and researchers of Southeast Asia Studies Ecologists About the Editors Cathrin Arenz coordinated the project "Grounding Area Studies in Social Practice: Southeast Asian Studies at Freiburg" before she joined a consultancy for climate mitigation projects in 2016. Dr. Michaela Haug is a member of the Dep. of Cultural and Social Anthropology at the University of Cologne. Stefan Seitz is professor emeritus of the Dep. of Social and Cultural Anthropology of the University of Freiburg. Dr. Oliver Venz worked at the Dep. of Anthropology and Sociology of the University of Malaya. Since 2017 he works at the Sarawak Museum Campus Project.